Local Wisdom in the Creative Economy of the Baduy Community - Supendi, Usman; Permana, Agus; Ruswanda, Asep Sandi; Samsudin, Samsudin (UIN Sunan Gunung Djati Bandung, 2025)
Local wisdom is cultural values ​​and traditions that are passed down from generation to generation, playing an important role in supporting the sustainability of the creative economy in the Baduy community. This study aims to examine how the local wisdom of the Baduy community is integrated into their creative economy practices, which include handicrafts, traditional weaving, and honey products. A qualitative approach was used in this study, with data collection through direct observation, in-depth interviews, and documentation studies. The results of the study indicate that the local wisdom of the Baduy community, such as the principle of living in harmony with nature and strict customary rules, is the main foundation in the production and marketing of their creative products. In addition, these values ​​also encourage environmental sustainability and maintain their cultural identity amidst the influence of modernization. This study concludes that the integration of local wisdom into the creative economy not only provides added value to the product, but also strengthens the social, cultural, and economic sustainability of the Baduy community.